2020
DOI: 10.1080/15476286.2019.1710054
|View full text |Cite
|
Sign up to set email alerts
|

The p53 family reaches the final frontier: the variegated regulation of the dark matter of the genome by the p53 family in cancer

Abstract: The tumour suppressor p53 and its paralogues, p63 and p73, are essential to maintain cellular homoeostasis and the integrity of the cell's genetic material, thus meriting the title of 'guardians of the genome'. The p53 family members are transcription factors and fulfill their activities by controlling the expression of protein-coding and non-coding genes. Here, we review how the latter group transcended from the 'dark matter' of the transcriptome, providing unexpected and intriguing anti-cancer therapeutic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 181 publications
(253 reference statements)
0
4
0
1
Order By: Relevance
“…LncRNAs constitute an ever-growing category of functional RNA species known to impinge on all hallmarks of cancer 33,52,53 . Here, we report the identification of two TAp63-regulated oncogenic lncRNAs or TROLLs, by using both genetically engineered and xenograft mouse models as well as a pan-cancer approach, including the analysis of 723 clinical cases and TCGA overall survival datasets.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs constitute an ever-growing category of functional RNA species known to impinge on all hallmarks of cancer 33,52,53 . Here, we report the identification of two TAp63-regulated oncogenic lncRNAs or TROLLs, by using both genetically engineered and xenograft mouse models as well as a pan-cancer approach, including the analysis of 723 clinical cases and TCGA overall survival datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The net result is decreased ubiquitination of p53, and thus increased level of p53 protein (Figure 7C ). Regulation of tumor suppressor p53 is essential for maintenance of genome integrity ( 72 , 73 ), innate immune response ( 74 ), stem cells and development ( 75 ). Interestingly, as a feedback regulation, MDM2 and members of TRIM family are high-confidence p53 target genes ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the biomarkers are commonly used in early screening for all kinds of cancers ( Yuan et al, 2020 ), and lncRNAs have attracted increasing attention as cancer biomarkers for early screening, diagnosis, prognosis, and responses to drug treatment ( Zhang et al, 2018 ; Necula et al, 2019 ; Zhuo et al, 2019 ). LncRNAs constitute an ever-growing category of functional RNA species known to impinge on all hallmarks of cancer ( Napoli and Flores, 2020 ). Many studies revealed that lncRNAs could regulate many important pathological processes in cancer, such as tumorigenesis, tumor progression, proliferation, metastasis, and drug resistance ( Fang and Fullwood, 2016 ; Schmitt and Chang, 2016 ), suggesting an enormous potential for further development of lncRNA biomarkers in specific cancer histologic analysis.…”
Section: Long Non-coding Rnas Serve As a Promising Target In The Trea...mentioning
confidence: 99%